American travelers on the Nile : early U.S. visitors to Egypt, 1774-1839 - Oliver, Andrew, Jr., 1936- (The American University in Cairo, 2014)
The Treaty of Ghent signed in 1814, ending the War of 1812, allowed Americans once again to travel abroad. Medical students went to Paris, artists to Rome, academics to Gottingen, and tourists to all European capitals. More intrepid Americans ventured to Athens, to Constantinople, and even to Egypt. Beginning with two eighteenth-century travellers, this book then turns to the 25-year period after 1815 that saw young men from East Coast cities, among them graduates of Harvard, Yale, and Columbia, travelling to the lands of the Bible and of the Greek and Latin authors they had first known as teenagers. Drawing on unpublished letters and diaries together with previously neglected newspaper accounts, as well as a handful of published accounts, this book offers a new look at the early American experience in Egypt and the eastern Mediterranean world. More than thirty illustrations complement the stories told by the travellers themselves.